Perbandingan Model Two-Tier dengan Three-Tier dalam Arsitektur Client/Server untuk Mengolah Perintah Query pada Aplikasi Database - Wahyu Pujiyono; M. Idham Ananta Timur; Savitri Savitri (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
In the client/server architecture, the increasing numbers of users tend to addmore complexity in database applications. As a result, performance will be the mainreason for managing database server with many users. Altough two-tier model can workwell by separating application from data sources, people always looking for anotheralternative to improve its performance and reability.Three-tier model is the next development of two-tier model which add the thirdcomponent within client application and application server, called “the middle tier.”Middle tier is placed in separate machine which has several functions. Do businessprocessing, and manage data are some of its useful functions. Separating businessprocessing machine from database server will improve its performance by using itsresources efficiently.This paper will compare the performance of two-tier model with three-tier modelin client/server architecture to manage query in database application developed byDelphi™. The connection process in three-tier model is focused on DCOMimplementation. As conclusion, three-tier model’s performance is more reliable and moreefficient than two-tier model in client/server architecture.Keywords: client/server database, two-tier, three-tier, query, DCOM.